De-Mystifying Mysticism: A Critical Realist Perspective on Ambivalences in the Study of Mysticism - Ali Qadir; Tatiana Tiaynen-Qadir (Religions)
The study of mysticism has been at an impasse for many years, wavering between naïve realism around a common core hypothesis and critical questioning of the category of mysticism and its imposition. In this article, we review key 20th century developments in the study of mysticism to understand why the term was largely abandoned and unpack the contours of this impasse. Specifically, we probe the literature to ask (i) how has mysticism been defined and (ii) who counts as a mystic? Our primary data are key pieces of scholarly literature on mysticism, including interdisciplinary studies and disciplinary literature from religious studies, history, philosophy, sociology, anthropology, and psychology. This review draws on a metatheoretic perspective of critical realism and is not meant to be comprehensive but rather analytical, seeking to identify patterns in scholarship. We find that each question is answered by studies along an axis, wavering between two ideal–typical poles. On the first question, we find scholarship ranging along an axis of essence between extreme poles of a reified vs. relativized substance of mysticism. On the second question, we find studies on an axis of access, varying between a rarified concept of mystical elites and a laified concept of mystical knowledge open to all. Putting studies along these axes yields a definitional space of mysticism that is compatible with critical realism and allows for the general study of mysticism to continue in a more nuanced, post-critique way. We also find that the category of experience lies at the origin or intersection point of both axes, and is a source of many problems in the general study of mysticism.